The 12 Gastrointestinal Pathogens Spectrum of Acute Infectious Diarrhea in a Sentinel Hospital, Shenzhen, China - Shen, Hongwei; Zhang, Jinjin; Li, Yinghui; Xie, Sirou; Jiang, Yixiang; Wu, Yanjie; Ye, Yuhui; Yang, Hong; Mo, Haolian; Situ, Chaoman; Hu, Qinghua (Frontiers in Microbiology, 2016)
Acute infectious gastroenteritis is one of the most common diseases among all ages, particularly in developing countries. The pathogen spectrum may differ among different regions and seasons. To investigate the etiology of acute diarrhea in Shenzhen, a prospective study was conducted from August 2014 to September 2015. Stools from 412 patients with diarrhea (286 of whom were adults) including the general epidemiological information of the patients were collected. The 19 pathogens were detected by conventional culture method or multiplex PCR assay, which included five viruses (rotavirus, adenovirus, sapovirus, norovirus, and astrovirus),11 bacterial pathogens (Salmonella, Campylobacter jejuni, Shigella, Listeria monocytogenes, Vibrio parahaemolyticus, Vibrio cholera, Enterohemorrhagic (EHEC), enteropathogenic (EPEC), enteroinvasive (EIEC), enterotoxigenic (ETEC); and enteroaggregative Escherichia coli (EAEC)) and three parasites (Entamoeba histolytica, Giardia lamblia, and Cryptosporidium parvum). A potential pathogen and coinfection was found in 41.5% and 7.0% of cases, respectively. The bacterial infection was the dominant cause of diarrhea (32.3%), and the three most frequently identified organisms were Salmonella (12.1%), ETEC (8.0%), and Campylobacter jejuni (4.9%). Salmonella enteritidis was the leading serotype of Salmonella spp.. Norovirus (8.3%) and sapovirus (2.2%) were the most common viral pathogens, followed by adenovirus (1.5%) and rotavirus (1.2%). The single most important causes of diarrhea were Salmonella spp. and Campylobacter jejuni, which points toward the need for testing and surveillance for these pathogens in this region.